Enhancement of energy efficiency by exhaust gas recirculation with oxygen-rich combustion in a natural gas combined cycle with a carbon capture process. (1st June 2020) - Lee, Woo-Sung; Kang, Jun-Ho; Lee, Jae-Cheol; Lee, Chang-Ha
Abstract: To enhance the energy efficiency in a natural gas combined cycle (NGCC) integrated with a chemical solvent-based carbon capture process (CCP), application of exhaust gas recirculation (EGR) with oxygen-rich (oxygen + air) combustion was studied. As the first step, performance of the CCP and its impact on the efficiency of the NGCC were evaluated by validated rigorous models. Net power generation of an NGCC with a CCP was 533 MW at 90% capture rate. Total capture cost was approximately 46.5 USD/ton of CO2 . When the EGR, known to improve the performance, was applied, enhancement of the net power generation was limited by 1% (538 MW) because utilization of excessive EGR can be a problem for stable operation of the gas turbine in NGCC. To further improve the EGR, therefore, feasibility of oxygen-rich (oxygen + air) combustion was investigated. The net power generation increased up to 555 MW, which improved about 4% than the original case. In addition, the results indicated that the unconditional mixing of oxygen can rather reduce the net power generation, and optimal composition of the oxygen-rich mixture gas is important. This study exhibited potential ways to improve the efficiency of an NGCC with a CCP. Highlights: A modified process to improve the efficiency of NGCC was studied by rigorous model. Total capture cost of an NGCC integrated with a CCP was 46.5 USD/ton of CO2 . Power enhancement by EGR was limited by 1% due to unstable operation of turbine. Oxygen-rich combustion integrated to EGR improved the net power generation by 4%.